An Analysis of Rural And Urban Areas Senior High School English Teachersâ€™ Ability In Developing Lesson Plan And Sylabus At Kolaka District - Ramli, Asyarifullah; Alberth, Alberth; Yazid, Muhammad (Halu Oleo University, 2018)
The aim of this study was to find out the ability, different abilities, and constraints encountered by English teachers at rural and urban areas in developing syllabus and lesson plan at Kolaka district. The study used the ex post facto method and a mixed method. Subjects of the study were all senior high school teachers of English in Kolaka district who had become civil servants. The syllabus and lesson plan were developed using KTSP curriculum. The study analyzed data quantitatively and qualitatively. Results of the study showed that the ability of the teachers in developing syllabus was 95%, or within a category of â€œvery good,â€ whereas their ability in developing lesson plan was 83%., which was categorized as â€œgood.â€ To look into the difference between rural teachersâ€™ ability and urban teachersâ€™ ability, a quantitative analysis was performed, and the result showed that, as far as the ability to develop syllabus and lesson was concerned, there was no difference between rural and urban teachers. To analyze constraints commonly encountered by these teachers, interviews were conducted, and the results suggested that there were some internal and external factors associated with this particular issue. It could be concluded that both urban and rural teachers were equally able to produce well-developed syllabus and lesson plan.